95gTc and 96gTc as alternatives to medical radioisotope 99mTc. Issue 1 (January 2018) - Hayakawa, Takehito; Hatsukawa, Yuichi; Tanimori, Toru
Abstract: We studied 95g Tc and 96g Tc as alternatives to the medical radioisotope 99m Tc. 96g Tc ( 95g Tc) can be produced by (p, n) reactions on an enriched 96 Mo ( 95 Mo) target with a proton beam provided by a compact accelerator such as a medical cyclotron that generate radioisotopes for positron emission tomography (PET). The γ-rays are measured with an electron-tracking Compton camera (ETCC). We calculated the relative intensities of the γ-rays from 95g Tc and 96g Tc. The calculated γ-ray intensity of a 96g Tc ( 95g Tc) nucleus is as high as 63% (70%) of that of a 99m Tc nucleus. We also calculated the patient radiation doses of 95g Tc and 96g Tc, which were larger than that of 99m Tc by a factor of 2–3 based on the applied assumptions. A medical PET cyclotron which can provide proton beams with energies of 11–12 MeV and a current of 100 μA can produce 12 GBq (39 GBq) of 96g Tc ( 95g Tc) for operation time of 8 h, which can be used for 240 (200) diagnostic scans.